The curse of the Marquis de Sade : a notorious scoundrel, a mythical manuscript, and the biggest scandal in literary history - Warner, Joel, 1978- (Crown, 2023)
"The captivating, deeply reported true story of how one of the most notorious novels ever written-Marquis de Sade's 120 Days of Sodom-landed at the heart of one of the biggest scams in modern literary history. Described as both "one of the most important novels ever written" and "the gospel of evil," 120 Days of Sodom was penned by the Marquis de Sade, a notorious eighteenth-century aristocrat who waged a campaign of mayhem and debauchery across France, evaded his own execution, and inspired the word "sadism," the term for receiving pleasure from pain. But of all his crimes, Sade considered 120 Days of Sodom his greatest transgression. Composed in the bowels of the Bastille in Paris, the tiny scroll on which it was written would embark on a centuries-spanning odyssey across Europe, passing from nineteenth-century banned book collectors to pioneering sex researchers to avant-garde artists and hidden away from Nazi book burnings. In 2014, the world heralded its return to France when it was purchased for millions by Gérard Lhéritier, the self-made son of a plumber who had used his savvy business skills to upend France's renowned rare book market. But soon the sale brought to light festering government vendettas, feuding antiquarian booksellers, manuscript sales derailed by sabotage, a record-breaking lottery jackpot, and allegations of a decade-long billion-euro con, the specifics of which, if true, would make the scroll part of France's largest-ever Ponzi scheme. Told with gripping reporting and flush with deceit and scandal, The Curse of the Marquis weaves together the sweeping odyssey of 120 Days of Sodom and the spectacular rise and fall of Lhéritier, once the "King of Manuscripts" and now known to many as the Bernie Madoff of France. At its center is an urgent question for all those who cherish the written word: As the age of handwriting comes to an end, what do we owe the original texts left behind?"--